Creating Honeypots to Prevent Online Child Exploitation - Joel Scanlan; Paul A. Watters; Jeremy Prichard; Charlotte Hunn; Caroline Spiranovic; Richard Wortley (Future Internet, 2022)
Honeypots have been a key tool in controlling and understanding digital crime for several decades. The tool has traditionally been deployed against actors who are attempting to hack into systems or as a discovery mechanism for new forms of malware. This paper presents a novel approach to using a honeypot architecture in conjunction with social networks to respond to non-technical digital crimes. The tool is presented within the context of Child Exploitation Material (CEM), and to support the goal of taking an educative approach to Internet users who are developing an interest in this material. The architecture that is presented in the paper includes multiple layers, including recruitment, obfuscation, and education. The approach does not aim to collect data to support punitive action, but to educate users, increasing their knowledge and awareness of the negative impacts of such material.